2013
DOI: 10.1002/jwmg.567
|View full text |Cite
|
Sign up to set email alerts
|

Survival and causes of mortality in a northern population of western gray squirrels

Abstract: We studied survival of radio-marked western gray squirrels (Sciurus griseus) and quantified causes of mortality including incidence and severity of notoedric mange in south-central Washington, 1998Washington, -2005. We used known-fate models in Program MARK to explore alternative hypotheses on factors related to survival and correlation analysis to investigate parameters that might be related to incidence of mange. The best-supported models indicated that survival varied by year and by sex and that survival o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Western gray squirrel females can give birth as 1‐year‐olds and males are scrotal (testes apparent outside of the body cavity) in their first spring (WDFW, unpublished data). We derived survival estimates for the Klickitat population using similar methods (Vander Haegen et al ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Western gray squirrel females can give birth as 1‐year‐olds and males are scrotal (testes apparent outside of the body cavity) in their first spring (WDFW, unpublished data). We derived survival estimates for the Klickitat population using similar methods (Vander Haegen et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Mange is caused by species of burrowing, sarcoptid mites that remain with the host through successive generations (Sweatman ). High mortality rates of western gray squirrels in Klickitat County, Washington, attributed to mange in 1998–1999 (Cornish et al ) likely constituted an epizootic where 53% of adult squirrels captured in spring were infested (Vander Haegen et al ); anecdotal reports provide evidence of an earlier epizootic in south‐central Washington during the 1930s (Rodrick , Linders and Stinson ). Although factors important to the epidemiology of the disease in tree squirrels are not known, Vander Haegen et al () reported a correlation between incidence of mange and mild winter temperatures that may promote survival of mites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oak masts failed and peaked every 2–4 years following productivity patterns typical of Oregon white oak (Peter and Harrington 2002, Devine and Harrington 2006), and a severe mast failure occurred in 2010, according to annual surveys (Peter and Harrington 2009) on the Base (D. H. Peter, U.S. Department of Agriculture Forest Service, unpublished data). Conifer mast failed the same year based on similar surveys of both Douglas‐fir and ponderosa pine on our study area (Vander Haegen and Orth 2011). During these mast failures, squirrels sought alternative food sources (Johnston et al 2019), including stripping of bark by western gray squirrels, indicating stressful conditions in 2010.…”
Section: Discussionmentioning
confidence: 67%
“…Intensive efforts to study and recover western gray squirrels on the Base began in 2007 because of increasing evidence that this population was vulnerable to extirpation (Ryan and Carey 1995, Bayrakçi et al 2001, Fimbel and Freed 2008). From 2007–2012, biologists augmented the population by releasing western gray squirrels translocated from other populations in Washington and Oregon, USA, and monitored their movements alongside resident squirrels with radio‐telemetry to investigate squirrel ecology and evaluate augmentation success (Vander Haegen and Orth 2011, Vander Haegen et al 2018). Concurrently, Johnston (2013) radio‐tracked eastern gray squirrels and experimentally removed some individuals to evaluate competitive interactions with western gray squirrels based on spatial partitioning, resource use, fitness correlates, diet (Johnston et al 2019), and behavior.…”
mentioning
confidence: 99%